THE EFFECT OF PRE-DEPARTURE TRAINING ON COMPETENCIES OF INDONESIAN INTERNSHIP PARTICIPANTS IN JAPAN - Rismaja Putra (CV. Radja Publika, 2024)
This study aims to analyze the effect of pre-departure training on the competency of Indonesian interns in Japan. A quantitative approach with a causal-associative survey design was used and supplemented with qualitative data through interviews. A sample of 60 pre-departure training students from five private Job Training Institutions (LPK) in Medan City was selected through purposive sampling with proportional allocation. Data were collected through a 1–5 Likert scale questionnaire, semi-structured interviews, and documentation, then analyzed using simple linear regression with IBM SPSS Statistics. The results of the study proved that pre-departure training had a positive and significant effect on the competency of interns (b = 0.765; t = 8.040; sig. = 0.000), with an explanatory power of 52.7% (R² = 0.527). Qualitative findings confirmed that Japanese language proficiency, practical portion, and work attitude development are central factors in competency formation. This research contributes quantitative empirical evidence in the context of international labor mobility, which has been dominated by qualitative studies, while also emphasizing the need for standardization of training quality between LPKs.